Job Shop Scheduling with Consideration of Due Dates Potentials of Local Search Based Solution Techniques - Kuhpfahl, Jens (Produktion und Logistik, 2016)
Jens Kuhpfahl analyzes the job shop scheduling problem with minimizing the total weighted tardiness as objective. First, he provides a suitable graph representation based on a disjunctive graph formulation. Second, several key components of local search procedures are analyzed and enhanced. The resulting outputs of these investigations contribute to the development of a new solution procedure whose performance quality leads to superior computational results. Contents Job Shop Scheduling - Formulation und Modelling Neighborhood Definitions for the JSPTWT Neighbor Evaluation Procedures Solving the JSPTWT - a new Solution Procedure Target Groups Researchers and students focusing on machine scheduling, operative production planning and control, as well as the development of powerful solution procedures Practitioners in these areas The Author Dr. Jens Kuhpfahl wrote his dissertation under the supervision of Prof. Dr. Christian Bierwirth at the Chair of Production and Logistics at the University of Halle (Saale).